POPULATION GENETIC STRUCTURE OF SPINY LOBSTERS, Panulirus homarus AND Panulirus ornatus, IN THE INDIAN OCEAN, CORAL TRIANGLE, AND SOUTH CHINA SEA - Gusti Ngurah Permana; Bedjo Slamet; Bagus Arya Permana; Ayu Krisna Dewi; Gusti Ngurah Mahardika (Indonesian Aquaculture Journal, 2019)
Populations of spiny lobsters worldwide are threatened by overfishing, while its supply from aquaculture is currently insufficient to meet the market demand. This current study investigated the genetic structure of two economically important spiny lobsters, P. homarus and P. ornatus sourced from the Indian Ocean and South China Sea. Fragments of the cytochrome oxidase subunit-I (COI) gene of the mitochondrial DNA of 71 P. homarus and 42 P. ornatus collected from 6 and 5 fish landing sites in Indonesia, respectively, were sequenced. Homologous sequences from the Indian Ocean and South China Sea available at GenBank were included in the analysis. No genetic differences were observed in P. ornatus populations from the two geographic regions (xST = -0.005) while a diminutive difference was found in the populations of P. homarus (xST = -0.002 and 0.009). These results, combined with a negative Tajima’s D estimates, points to a deficit of nucleotide variation relative to the expectations from the mutation/drift equilibrium. Reconstruction of the phylogeny of P. homarus demonstrates that all Indonesian samples of P. homarus are grouped in one cluster and share the common cluster with GenBank data originated from Taiwan, Vietnam, India, Sri Lanka, Oman, and Iran. The phylogeny of P. ornatus indicates that there are two separated lineages existing in Indonesia.